2000
DOI: 10.1108/02637470010348744
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction level with neighbourhoods in low‐income public housing in Yemen

Abstract: For the last 20 years, the Yemeni government has been providing housing schemes for low‐income groups. These low‐income housing schemes have not, however, been evaluated. Based on a post‐occupancy evaluation of three low‐income public housing schemes in Sana’a, Yemen, the paper describes the residents’ judgement and assessment of the environment in which they are living. Interviews with 180 occupants revealed that they attach great importance to the level of satisfaction with their neighbourhoods. The most imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 10 publications
1
56
0
2
Order By: Relevance
“…Nurizan (1993) reported that whereas the residents of low-cost housing in Johor Bahru were satisfied with public transport and the distance of housing from the city, they were not satisfied with the size, rent and crowding in their houses. Djebarni and Al-Abed (2000) observed that the residents of public low-income housing in Sana'a attach great importance to the level of satisfaction with their neighbourhoods, particularly with regard to privacy, which reflects the cultural background of Yemeni society. Lane and Kinsey (1980) reported that housing characteristics were more crucial determinants than demographic characteristics of housing occupants.…”
Section: Perspectives On Housing Satisfaction Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Nurizan (1993) reported that whereas the residents of low-cost housing in Johor Bahru were satisfied with public transport and the distance of housing from the city, they were not satisfied with the size, rent and crowding in their houses. Djebarni and Al-Abed (2000) observed that the residents of public low-income housing in Sana'a attach great importance to the level of satisfaction with their neighbourhoods, particularly with regard to privacy, which reflects the cultural background of Yemeni society. Lane and Kinsey (1980) reported that housing characteristics were more crucial determinants than demographic characteristics of housing occupants.…”
Section: Perspectives On Housing Satisfaction Literaturementioning
confidence: 99%
“…The idea of housing satisfaction has been used as a guide by many planners, designers, developers and policy-makers who attempt to provide housing to a variety of people (Ukoha and Beamish 1997). It has been used as (a) a key predictor of an individual's perceptions of general quality of life; (b) an indicator of incipient residential mobility, and has thereby altered housing demands and affected neighbourhood change; (c) an ad hoc evaluative measure for judging the success of developments constructed by private and public sectors; and (d) a tool to assess residents' perceptions of inadequacies in their current housing environment in order to improve the status quo (Djebarni and Al-Abed 2000). Recently, the neighbourhood component of housing satisfaction has been used to evaluate the physical form of two US cities (Yang 2008).…”
Section: Perspectives On Housing Satisfaction Literaturementioning
confidence: 99%
“…Some factors of residential buildings do not exist in the university dormitory context, such as ownership and ways to purchase [26,27], distance to work, location of schools [28], building age and safety [29], satisfaction with community services [30] and neighbors [16,31]. In addition, difference also lies into the demographic background of the occupants [32], such as number of family members [16,23,33].…”
Section: Introductionmentioning
confidence: 99%
“…Se ha usado el tipo de vivienda, el tipo de colonia, la condición migratoria, así como otras variables regionales, demográficas y socioeconómicas. En particular se ha estudiado cómo difiere la satisfacción con la colonia de: los residentes locales y los extranjeros (Li, 2012;Oktay et al, 2012); los residentes beneficiarios de programas de vivienda gubernamentales en áreas urbanas frente a los de los sitios suburbanos (Cook, 1988); los residentes en áreas centrales en comparación con los que viven en la periferia de las áreas centrales (Loo, 1986); los residentes en suburbios convencionales respecto a los que viven en colonias que tienen diseños tradicionales (Lavejoy et al, 2010); las personas que residen en colonias con dife-rentes esquemas o tipos de vivienda (Djebami y Al-Abed, 2000;Gruber y Shelton, 1987); los residentes de acuerdo con su raza (Greif, 2009;Lee et al, 1991;Hunter, 1974;Campbell et al, 1976;Fried, 1982;Ahlbrandt, 1984); las comunidades compactas frente a las mixtas, que concentran los lugares de empleo y vivienda, así como el uso eficiente del suelo y la reducción de las distancias (Yang, 2008); las comunidades que cobran cuotas de mantenimiento en contraposición con aquellas que no tienen esa práctica (Chapman y Lombard, 2006). Asimismo se ha analizado la influencia de las características sociodemográficas y el tipo de colonia (clasificadas en áreas afluentes y desfavorecidas) en el grado de satisfacción con la colonia (Hipp, 2009;Parkes et al, 2002), así como la influencia de la mezcla de residentes, en términos del régimen de propiedad en la colonia (Kearns y Mason, 2007).…”
Section: Literatura En Torno a La Satisfacción Con La Coloniaunclassified